Endocrine profile and embryo quality of cows superovulated with super-Ov following hCG and estradiol-17β pretreatment - KHARCHE, S D; SHARMA, G TARU; AGARWAL, S K; MAJUMDAR, A C; SHARMA, N C; SANWAL, P C (The Indian Journal of Animal Sciences, 2014)
Pretreatment effect of hCG and estradiol-1713 on superovulatory response embryo quality and embryo recovery by exogenous administration of FSH was studied in 15 adult cyclic crossbred cows randomly divided in 3 groups. Group Ianimals received 60 ru super-Ov in 6 dosd of constant 3 days schedule from day 11 of cycle; 25 mg of PGF p was injected with last FSH injection. Group 2 animals received 250 IU hCG (im) on day 9 and 2 mg estradiol (sc) on day 10 followed by superovulation on day 11. Group 3 animals received 500 IU hCG in place of250 IU hCG. Other treatments were similar to that of group 2 animals. Animals were inseminated at 0, 12 and 24 hr after onset of estrus. The ovarian response and embryo quality were recorded after non surgical collection on day 8. Blood plasma collected during the experiments was subjected FSH and progesterone estimation.   Ovulation rate did not differ significantly among the different treatment groups. However, comparatively large number of transferable embryos were recorded with the 250 IU hCG and estradiol pretreatment (3.00± 1.09) in comparison to control (0.40±0.42) or 500 IU hCG (0.80±0.58). Increased FSH level on estrus and progesterone on day of flushing was positively correlated with transferable embryos. It may be concluded that pretreatment of low dose of hCG and estradiol prior to superovulatory treatment probably develops more follicles and ovulate synchronously, thus enhances transferable embryo production.